2020 IEEE International Conference on Pervasive Computing and Communications Workshops (PerCom Workshops) 2020
DOI: 10.1109/percomworkshops48775.2020.9156105
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal Co-Presence Detection with Varying Spatio-Temporal Granularity

Abstract: Pervasive computing environments are characterized by a plethora of sensing and communication-enabled devices that diffuse themselves among different users. Built-in sensors and telecommunication infrastructure allow co-presence detection. In turn, co-presence detection enables context-aware applications, like those for social networking among close-by users, and for modeling human behavior. We aim to support developers building better context-aware applications by a deepened understanding of which set of cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…The paper by [6] described another way to accomplish how a tracking system works with a camera-based hand-held system. Moreover, the researchers could obtain Bluetooth communication through various topics such as object tracking, child monitoring, and location detection [7][8][9]. Existing research [10][11][12][13] has shown how GPS could be interpreted through various aspects and combine multiple systems [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…The paper by [6] described another way to accomplish how a tracking system works with a camera-based hand-held system. Moreover, the researchers could obtain Bluetooth communication through various topics such as object tracking, child monitoring, and location detection [7][8][9]. Existing research [10][11][12][13] has shown how GPS could be interpreted through various aspects and combine multiple systems [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…In another aspect addressed in this work, it is noted that handling of multi-user location information over extended periods of time generates large volumes of spatio-temporal data, which highlights the need for compact data representations [25][26][27][28]. Processing techniques applied to proximity and community detection [29][30][31], and trajectory similarities and cluster formations [32][33][34] have also been of interest recently. For our purpose, emphasis is placed on applying low-complexity reduction to achieve a balanced tradeoff between data compression savings and retained accuracy in mobiles' proximity detection.…”
Section: Introductionmentioning
confidence: 99%